Improving the effectiveness of public administration of the Republic of Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
The article dedicated to the activities of the state to improve the effectiveness of public administration of the Republic of Kazakhstan. Improving the effi ciency and effectiveness of public administration in the present conditions are of particular importance. It provides a political analysis of the need to phased implementation of various methods of increasing the effectiveness of the controls. Specifi cally, elaborating the normative documents and implementation of the system performance evaluation of state bodies. Keywords: effi ciency of public administration, administrative reform, strategic objectives, performance evaluation system of state authorities.